Bound in captivity: intersections of viking raiding, slaving, and settlement in Western Europe during the ninth century CE. (8th August 2022) - Raffield, Ben
ABSTRACT: The Viking Age (c. 750–1050 CE) was a time of extensive upheaval and disruption across the northern world. From the late eighth century, historical sources indicate that viking groups were engaging in both short-term and extended campaigns of raiding and plunder. In addition to seeking portable wealth and commodities, it is apparent that raiders also sought captives, many of whom were taken and held in encampments where they were ransomed, exploited, or sold into slavery. While these sites served an important function as defensive strongholds and staging posts for viking raiding activity, recent studies have demonstrated that they were also militarized centres of production and exchange that, in some cases, became nodal marketplaces that were embedded within both regional and long-distance networks of communication and trade. Focusing in particular on the ninth century, this study will examine the ways in which captive-taking and slaving intersected with the emergence and development of these locales, as well as the role of these activities in shaping wider processes of communication, diplomacy, and cross-cultural interaction within landscapes of conflict and settlement.